Towards a molecular taxonomic key of the Aurantioideae subfamily using chloroplastic SNP diagnostic markers of the main clades genotyped by competitive allele-specific PCR - Oueslati, Amel; Ollitrault, Frederique; Baraket, Ghada; Salhi-Hannachi, Amel; Navarro, Luis; Ollitrault, Patrick (Springer, 2020)
Background Chloroplast DNA is a primary source of molecular variations for phylogenetic analysis of photosynthetic eukaryotes. However, the sequencing and analysis of multiple chloroplastic regions is difficult to apply to large collections or large samples of natural populations. The objective of our work was to demonstrate that a molecular taxonomic key based on easy, scalable and low-cost genotyping method should be developed from a set of Single Nucleotide Polymorphisms (SNPs) diagnostic of well-established clades. It was applied to the Aurantioideae subfamily, the largest group of the Rutaceae family that includes the cultivated citrus species. Results The publicly available nucleotide sequences of eight plastid genomic regions were compared for 79 accessions of the Aurantioideae subfamily to search for SNPs revealing taxonomic differentiation at the inter-tribe, inter-subtribe, inter-genus and interspecific levels. Diagnostic SNPs (DSNPs) were found for 46 of the 54 clade levels analysed. Forty DSNPs were selected to develop KASPar markers and their taxonomic value was tested by genotyping 108 accessions of the Aurantioideae subfamily. Twenty-seven markers diagnostic of 24 clades were validated and they displayed a very high rate of transferability in the Aurantioideae subfamily (only 1.2 % of missing data on average). The UPGMA from the validated markers produced a cladistic organisation that was highly coherent with the previous phylogenetic analysis based on the sequence data of the eight plasmid regions. In particular, the monophyletic origin of the “true citrus” genera plus Oxanthera was validated. However, some clarification remains necessary regarding the organisation of the other wild species of the Citreae tribe. Conclusions We validated the concept that with well-established clades, DSNPs can be selected and efficiently transformed into competitive allele-specific PCR markers (KASPar method) allowing cost-effective highly efficient cladistic analysis in large collections at subfamily level. The robustness of this genotyping method is an additional decisive advantage for network collaborative research. The availability of WGS data for the main “true citrus” species should soon make it possible to develop a set of DSNP markers allowing very fine resolution of this very important horticultural group.